2009
DOI: 10.1007/s11605-008-0753-y
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Effectiveness of a New Algorithm in Preventing Hepatic Artery Thrombosis after Liver Transplantation

Abstract: Therefore, we have implemented the presented algorithm, which showed an acceptable HAT rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
(49 reference statements)
0
7
0
Order By: Relevance
“… 8 , 9 Previous history of HAT, low donor body weight, and complex arterial reconstruction have been described as risk factors for the development of HAT. 4 , 10 - 12 In an attempt to prevent HAT, all current adult LT recipients are placed on long-term antiplatelet therapy with low-dose aspirin which may have contributed to lower the incidence of HAT from 7.6% to 6.5% at our institution. 4 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 , 9 Previous history of HAT, low donor body weight, and complex arterial reconstruction have been described as risk factors for the development of HAT. 4 , 10 - 12 In an attempt to prevent HAT, all current adult LT recipients are placed on long-term antiplatelet therapy with low-dose aspirin which may have contributed to lower the incidence of HAT from 7.6% to 6.5% at our institution. 4 …”
Section: Discussionmentioning
confidence: 99%
“…Conservative management of L-HAT is only successful in a minority, and many L-HAT patients are either too sick to be relisted or die on the waiting list. 12 , 18 In fact, although it is reported that the incidence of L-HAT exceeds the occurrence of early HAT, re-LT for L-HAT is less common. 4 …”
Section: Discussionmentioning
confidence: 99%
“…We performed a post hoc analysis of a prospectively conducted registry database study ( 4 ) on adult patients who underwent orthotopic liver transplantation at our center between January 1st, 2004 and December 31st, 2017, to assess whether perioperative PCC or fibrinogen administration is associated with thrombotic complications. Patients were included if enrolled in the surgical database and anesthesia and intensive care unit (ICU) records were available.…”
Section: Methodsmentioning
confidence: 99%
“…Thrombotic events after liver transplantation are serious complications associated with an adverse outcome. Hepatic artery thrombosis (HAT), portal vein thrombosis (PVT), and thrombosis of the inferior vena cava occur at frequencies of up to 9, 2, and 2%, respectively (1)(2)(3)(4). HAT can further be divided into early (occurring within 1 month after liver transplantation) or late HAT events (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation